The Effectiveness of Using Booklets towards Knowledge and Compliance with Iron Tablet Consumption among Pregnant Women at Guguk Panjang Public Health Center, Bukittinggi City - Meilinda Agus; Lisma Evareny (Universitas Andalas, 2022)
Anemia in pregnancy can cause complications in childbirth, in 2018 anemia in pregnant women in Indonesia was 48.9%. The government's efforts to overcome anemia is by providing iron tablets. The latest data showed that 34% of pregnant women have not taken iron tablet for less than 90 days, for reason forgot as many as 21.8%. Based on previous results, the booklet was considered very effective in overcoming the problem of anemia. Based on 2018 report in Guguk Panjang Public Health Centre there were 647 pregnant women with anemia. To see the effectiveness of using booklets at the Guguk Panjang Health Center Bukittinggi city.This study used a one-group pre-test post-test design, which was experimental method. The population in this study were pregnant women in the working area of Guguk Panjang Public Health Centre, Bukittinggi City. The number of samples was 31 respondents with accidental sampling technique.This study was conducted with the t test, to determine before and after using the booklet the Wilcoxon Signed Ranks Test was conducted. Based on the results of this study, normal distribution can be seen on pre-test knowledge = 0.166, post-test knowledge = 0.001, pre-test adherence = 0.000, post-test adherence = 0.000. For the provision of booklets there is an increase in knowledge of Z = -3,879 with a value of p = 0.000. There is an increase in adherence = -2.239 with p value = 0.025. It can be concluded that there is an increase in knowledge and compliance of pregnant women by using booklets at the Guguk Panjang Health Center, Bukittinggi City.